2015
DOI: 10.1542/peds.2014-1906
|View full text |Cite
|
Sign up to set email alerts
|

Morphine or Ibuprofen for Post-Tonsillectomy Analgesia: A Randomized Trial

Abstract: BACKGROUND: Pediatric sleep disordered breathing is often caused by hypertrophy of the tonsils and is commonly managed by tonsillectomy. There is controversy regarding which postsurgical analgesic agents are safe and efficacious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(138 citation statements)
references
References 33 publications
2
125
1
6
Order By: Relevance
“…Our results are consistent with those from a study of children with nonoperative fractures in which oral morphine produced analgesia comparable to that with ibuprofen but had significantly more adverse effects. 22 In children remaining in hospital after surgery, several studies have found that parenteral 46 and oral morphine 47,48 did not produce better analgesia than active comparators. Our findings contribute to this evidence, because we have shown that after discharge from ambulatory surgery, oral morphine has no analgesic advantage over ibuprofen for first-line treatment of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those from a study of children with nonoperative fractures in which oral morphine produced analgesia comparable to that with ibuprofen but had significantly more adverse effects. 22 In children remaining in hospital after surgery, several studies have found that parenteral 46 and oral morphine 47,48 did not produce better analgesia than active comparators. Our findings contribute to this evidence, because we have shown that after discharge from ambulatory surgery, oral morphine has no analgesic advantage over ibuprofen for first-line treatment of pain.…”
Section: Discussionmentioning
confidence: 99%
“…La douleur associée à l'amygdalectomie est considérée comme modérée à sévère 6 . Actuellement, il n'y a pas de consensus quant au meilleur analgésique à utiliser dans ce contexte 11,12 .…”
Section: Douleursunclassified
“…Des cas d'hospitalisation et de décès ont été rapportés parmi des enfants ultramétabolisateurs ou métabolisateurs extensifs du cytochrome P450 2D6 ayant souffert d'apnée du sommeil et ayant reçu de la codéine pour le soulagement de la douleur après une amygdalectomie, ce qui a mené Santé Canada à restreindre l'usage de la codéine 1,2,27 . Chez les patients ayant un trouble respiratoire du sommeil, l'usage d'opiacés à la suite d'une amygdalectomie diminue davantage le taux de saturation d'oxygène sanguin postopératoire comparativement à l'ibuprofène 6 . L'efficacité de la morphine, quant à elle, ne dépend pas des cytochromes P450.…”
Section: Douleursunclassified
See 2 more Smart Citations